2016
DOI: 10.1088/1475-7516/2016/11/031
|View full text |Cite
|
Sign up to set email alerts
|

Generalized dark energy interactions with multiple fluids

Abstract: Abstract. In the search for an explanation for the current acceleration of the Universe, scalar fields are the most simple and useful tools to build models of dark energy. This field, however, must in principle couple with the rest of the world and not necessarily in the same way to different particles or fluids. We provide the most complete dynamical system analysis to date, consisting of a canonical scalar field conformally and disformally coupled to both dust and radiation. We perform a detailed study of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 55 publications
2
60
0
Order By: Relevance
“…IV we follow to rewrite the equations as a dynamical system in terms of dimensionless variables with physical interest and proceed to the study of the single-fluid scenario for both pressureless and relativist fluids. Additionally we comment on the novelties associated with the introduction of the kinetic dependence, in contrast with [77] and also comment on some of the "pathologies" and features found in previous works. In Sec.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…IV we follow to rewrite the equations as a dynamical system in terms of dimensionless variables with physical interest and proceed to the study of the single-fluid scenario for both pressureless and relativist fluids. Additionally we comment on the novelties associated with the introduction of the kinetic dependence, in contrast with [77] and also comment on some of the "pathologies" and features found in previous works. In Sec.…”
mentioning
confidence: 83%
“…• If µ = 0 the system reduces to disformally coupled quintessence, in the case where the conformal and disformal functions depend only on the field itself. This was studied in [59,77].…”
Section: Dynamical Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially these interacting models invoke energy exchange between the dark components and a small degree of momentum exchange. These scenarios have been intensively investigated in the literature for several dark sector coupling functions and observational approximations [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It has recently been shown that the current observational data can favor the late time interaction between DE and DM [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to transform general scalar-tensor theories to Einstein frame, we need transformations that are more general than the conformal transformation. It has been shown that subclasses of the GLPV theory which is the generalization of the Horndeski theory can be transformed to the Einstein frame using the disformal transformation defined as [19][20][21] g μν = C(φ)g μν + D(φ, X )φ ,μ φ ,ν ,…”
Section: Introductionmentioning
confidence: 99%